A Vision of Kuala Lumpur 2040 - Lyn, Tan Yee (MAJ - Malaysia Architectural Journal, 2025)
In November 2023, Kuala Lumpur Structure Plan (KLSP) 2040 was launched, emphasizing a vision of a green, healthy, and vibrant city - a city that promotes an active lifestyle through natural environments like forests and parks and revitalizing urban spaces with cultural activities reflecting Kuala Lumpur's identity. However, with unconnected public infrastructure, overdeveloped skyscrapers, and limited green areas, this paper aims to discuss the city's sustainable development to accommodate the growing 2.1 million to 2.35 million population by 2040 to achieve its goals.